Physical Activity and Climacteric Symptoms Among Premenopause Women - Sari, Devi Permata; Hamranani, Sri Sat Titi; Supardi, Supardi; Damayanti, Fera (Journal of Nursing Science Update (JNSU), 2024)
Women experience physical changes before menopause. Women experience climacteric conditions caused by decreased reproductive hormones, so they experience the climacteric period. Climacteric is 4-5 years that occurs before menopause. Women experience problems during the climacteric period, such as hot flashes, sleep disorders, mood swings, and increased osteoporosis. Physical activity with conscious body movements produced by skeletal muscles requires energy expenditure. Physical activity includes all activities, with the intensity to help climacteric symptoms. This research aimed to identify the correlation between physical activity and climacteric symptoms. This research design used an analytical study with a cross-sectional approach. The sample was 72 women of premenopausal age, and it was obtained by cluster sampling. The research instrument was a questionnaire. The data analysis was the Kendal Tau test. The results of this study were 44.86 ± 3.041%, and the average number of children in this study was 2.76 ± 1.157%, elementary school education level was 47.2%, unemployed was 81.9%, respondents who did not use contraception hormonal and non-hormonal as many as 86.1%, respondents who did high physical activity were 93.1%, and respondents who did not have climacteric symptoms were 97.2%. The results of the Kendal Tau test showed a value (ρ value = 0.000), so there was a relationship between physical activity and climacteric symptoms in premenopausal women. In conclusion, physical activity has a relationship with climacteric symptoms in premenopausal women